Perspectives on returning individual and aggregate genomic research results to study participants and communities in Kenya: a qualitative study - Kisiangani, I.; Mohamed, S.F.; Kyobutungi, C.; Tindana, P.; Ghansah, A.; Ramsay, M.; Asiki, G. (BMC Medical Ethics, 2022)
Background: A fundamental ethical challenge in conducting genomics research is the question of what and how individual level genetic findings and aggregate genomic results should be conveyed to research participants and communities. This is within the context of minimal guidance, policies, and experiences, particularly in Africa. The aim of this study was to explore the perspectives of key stakeholders’ on returning genomics research results to participants in Kenya. Methods: This qualitative study involved focus group discussions (FGDs) and in-depth interviews (IDIs) with 69 stakeholders. The purposively selected participants, included research ethics committee (REC) members (8), community members (44), community resource persons (8), and researchers (9). A semi-structured interview guide was used to facilitate discussions. Six FGDs and twenty-five (IDIs) were conducted among the diferent stakeholders. The issues explored in the interviews included: (1) views on returning results, (2) kind of results to be returned, (3) value of returning results to participants, and (4) challenges anticipated in returning results to participants and communities. The interviews were audio-recorded, transcribed verbatim, and coded in Nvivo 12 pro. Thematic and content analysis was conducted. Results: Participants agreed on the importance of returning genomic results either as individual or aggregate results. The most cited reasons for returning of genomic results included recognizing participants’ contribution to research, encouraging participation in future research, and increasing the awareness of scientific progress. Other aspects on how genomic research results should be shared included sharing easy to understand results in the shortest time possible and maintaining confidentiality when sharing sensitive results. Conclusions: This study identified key stakeholders’ perspectives on returning genomic results at the individual and community levels in two urban informal settlements of Nairobi. The majority of the participants expect to receive feedback about their genomic results, and it is an obligation for researchers to see how to best fulfil it.
Research Article
Keywords: Genomics; Return of results; Aggregate level; Individual level